COVID 19, neuropsychiatric symptoms and pathophysiological mechanisms. A narrative review - González C., Rodrigo (Revista de Psiquiatría Clínica, 2022)
We are currently experiencing a pandemic caused by SARS COV 2, a virus that causes the COVID 19 disease. Both the manifestations of the disease and those derived from epidemiological conditions have reported a high incidence of neuropsychiatric manifestations, for this reason the challenge of differentiating between direct affectation or indirect effect of disease and the pathological mechanisms that underlie them is necessary in order to improve diagnoses and treatments, as well as to recognize the impact caused by living conditions during the pandemic, risk factors and future projections is a necessary work in order to optimize isolation measures and prepare us to face the consequences that the pandemic will have on our population.